The Role of Green Economy in the Sustainable Development of Agro-Industrial Complex: Evidence from Uzbekistan - Chorievich, Boboev Akmal; Idievna, Kurbonova Khurshida; Barotovich, Ochilov Sherali; Makhsudovich, Amonov Zamirbek; Nematovich, Berdiev Golib; Xolmurotov, Fozil; Xolmuratov, Xolilla (International Journal of Energy Economics and Policy, 2026)
This study investigates the impact of green economy factors on the sustainable development of Uzbekistan’s agro-industrial complex using annual data from 1991 to 2024. The analysis focuses on key determinants such as electricity consumption, mineral fertilizer use, inflation, and renewable energy production, with the food production index serving as the dependent variable. Applying the Autoregressive Distributed Lag (ARDL) model, both short- and long-run relationships were examined. The results demonstrate that renewable energy production and rational fertilizer use significantly enhance food production in the long term, while inflation exerts a negative influence, undermining production sustainability. Electricity consumption, however, showed no statistically significant long-run effect, highlighting that resource efficiency and diversification of energy sources are more crucial than total consumption. These findings underscore the strategic importance of green economy principles in strengthening food security, reducing environmental risks, and ensuring the resilience of the agro-industrial sector in Uzbekistan. The study provides empirical evidence to support policy measures aimed at expanding renewable energy use, promoting sustainable fertilizer management, and curbing inflationary risks to achieve long-term agricultural sustainability.